England : The state of the regions - Mawson, John; Tomaney, John, 1963- (Book collections on Project MUSE., 2002)
This authoritative book provides the first up-to-date and comprehensive picture of the state of regionalism in England. Policy makers, practitioners, academics, students, journalists and others who need to understand and keep up to date with the development of governance of the English regions will find this book to be an indispensable resource.